Penggunaan Penggunaan Aplikasi SPSS dalam Pembelajaran Mata Kuliah Statistika Pendidikan di INSURI Ponorogo untuk Meningkatkan Motivasi Belajar Mahasiswa - mu'ti, yafita (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The educational statistics course is a mandatory subject that students majoring in education or Tarbiyah must take. This course helps students complete final assignments or theses for those who take a quantitative approach. Educational statistics courses have a high level of difficulty because they study how to collect, present, process, analyze and conclude data. To overcome this problem, learning innovations are provided by using the SPSS application in the learning process of educational statistics courses. The aim of this research is to find out how the SPSS application is used in the learning process of the Education Statistics course at INSURI Ponorogo. The research methods used are observation, interviews and documentation. The data analysis technique involves triangulation in collecting information, data analysis is carried out inductively, and conclusions are drawn up at the Sunan Giri Islamic Institute (INSURI), Ponorogo. The research results show that students are motivated, interested and like learning using the SPSS application. The SPSS application needs to be applied in the learning process to improve student learning outcomes in all faculties at INSURI Ponorogo.